Use of drugs against osteoporosis in the Baltic countries during 2010–2014 - Ott Laius; Katre Maasalu; Sulev Kõks; Aare Märtson (Medicina, 2016)
Background and objective: Osteoporosis is a major health threat nowadays. Aging of the population and changes in peoples’ lifestyle result in a constant increase in the number of fractures all over the world. Our study aimed at describing the drug utilization pattern and choice of active substances of antiosteoporotic medicines in the Baltic countries. Materials and methods: Sales data of the antiosteoporotic medicines was obtained from the internet. These are available on the website of medicines regulatory agencies. The World Health Organization (WHO) methodology of Anatomical Therapeutic Chemical (ATC) classification and defined daily dose (DDD) was used to compare the data among countries. Results: During the study period the consumption of antiosteoporotic medicines was rather stable in all the countries. The overall choice of active substances used to treat osteoporosis is similar in all the Baltic countries but the market shares of substances were different. Estonia stands out with high use of combination product of alendronic acid and colecalciferol. In Latvia the highest consumption was of risedronic acid. In Lithuania the most used active substance in 2014 was ibandronic acid and second was denosumab with 0.8 daily doses per 1000 inhabitants per day (DID) and 25% of the total share. Conclusions: The differences in consumption of drugs against osteoporosis in the Baltic countries are not very big. The consumption of antiosteoporotic drugs is not to be regarded as sufficient though. The generally low consumption of osteoporotic medicines in the Baltic countries can be attributed to the overall less than EU average wealth of the countries and less than optimal expenditure on healthcare out of the GDP.